PSYCHOLOGICAL DAMAGE TO MEDICAL STAFF DUE TO SARS - COV-2 VIRUS - Heidrun ADUMITRĂCHIOAIEI; Alina-Costina LUCA (Cross-Cultural Management Journal, 2022)

(untitled)
Based on the evidence showing the psychological impairment of medical staff in pandemic periods is useful to introduce large-scale support programs and psychological education of medical staff. These measures, adapted to age and sex, can help increase the quality of work in the health fields and can also prevent medical leave for employees due to psychiatric pathologies caused by poorly managed stress and burnout.